COMPARISON OF THE EFFECTIVENESS OF MOVIE MEDIA AND PUPPET STORY TOWARD DENTAL AND ORAL HYGIENE IN ELEMENTARY SCHOOL STUDENTS IN SEMARANG - Ediyarsari, Puput; Made Sudana, I; Ratna Rahayu, Sri (Public Health Perspective Journal, 2020)
Dental and oral disease will greatly affect the degree of health, the process of growth and development even the child's future. The success of maintaining dental and oral health is influenced by the method of brushing teeth, the frequency and time of proper brushing. The purpose of this study was to compare the effectiveness of movie media with puppet stories in elementary school students. This research design is quantitative with a quasi-experimental design consisting of a movie media intervention group, a puppet story intervention group and a control group. Each group sample was 56 students with a total population of 168 students. The sampling technique for the control group used purposive sampling while the intervention group used total sampling technique. Dental and oral hygiene education with puppet stories is more effective than movie media with a Mean Rank value of movie media 50.50, Mean Rank of puppet stories is 62.50 and a Significance value of 0.023 which means it is smaller than the level of significance ? <0.05. From this study it can be concluded that the average value of puppet stories is greater than the average value of movie media. So that this method can be a means of developing knowledge in the field of public health, especially about the promotion of dental and oral health in children © 2020 Semarang State University